An Exposition of Nehemiah 5:7-8 and Its Implications for Nigeria’s Socio-Economic Development - Lawal, Joseph Owolabi (KWASU Journal of Religious Studies, 2017)
Leadership has become a serious problem in Nigeria. This makes the nation to suffer a deficit of civic pride and collective responsibility. This paper attempts a comparative analysis of leadership style advocated by Nehemiah as a onetime governor of Judea. It adopts an exposition of Nehemiah 5:7-8 where Nehemiah's leadership by example, patriotism and selflessness are emphasized. Also, Nehemiah showcases the divine call to a sacred duty. The paper concludes that the quality of leadership in any organization affects greatly the success or failure of that organization. It recommends that for Nigeria to experience prosperity in the midst of her abundant human and mineral resources, her leaders must be ready to live above board.